2016
DOI: 10.1515/rehab-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Obesity among adults with moderate and severe intellectual disabilities

Abstract: Introduction: Obesity is a common health problem among adults people with intellectual disabilities. The aim of the present study was to determine the prevalence of obesity among people with moderate and severe intellectual disabilities by gender, age and degree of disability. Material and methods: The study group comprised 194 individuals with moderate and severe intellectual disability, aged 20 to 50 years. They were all participants of an occupational therapy workshop. Measurements of height and body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The results of this study showed that excess body weight was observed in 66.7% and obesity in 38.9% of the respondents (seven subjects). Other Polish study also indicated high prevalence of obesity among people with ID [9]. This is comparable to the results of the present research conducted among the younger population.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study showed that excess body weight was observed in 66.7% and obesity in 38.9% of the respondents (seven subjects). Other Polish study also indicated high prevalence of obesity among people with ID [9]. This is comparable to the results of the present research conducted among the younger population.…”
Section: Discussionsupporting
confidence: 91%
“…The present study did not find any differences in the occurrence of excess body weight depending on gender, basic diagnosis, or the severity of ID. Similarly, in the studies by Gawlik et al [9] and De et al [37], no correlation was noticed between the nutritional status and the grade of ID. In the study of Hoey et al [1], waist circumference was observed to increase with an increase in the degree of impairment, but no such correlation was found with BMI.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations